Studi Mengenai Gambaran Subjective Well-Being pada Ibu Pekerja Selama Masa Pandemi Covid-19 - Yulia Putri Pratiwi (Jurnal Riset Psikologi, 2021)
Abstract. The Covid-19 pandemic has had a significant impact on the subjective well-being of working mothers who work from home. The Covid-19 pandemic situation provides complex conditions for working mothers who work from home, then this situation causing distress, where mothers have to monitor and control their children's schoolwork, household tasks, and are required to work remotely from home. This has a psychological impact on a mother, one of which is subjective well-being. The purpose of this study is to see how the subjective well-being of a working mother who works from home during the Covid-19 pandemic in Bandung City. This study uses a qualitative method with a quantitative approach. The sample in this study was 300 people, using purposive sampling technique. Measurement of subjective well-being is obtained through two measuring tools from Diener, namely the Satisfaction With Life Scale (SWLS) which has been adapted by Yusak Novanto and the Scale of Positive and Negative Experience (SPANE). The results of the two measuring tools show that 70% of the subjective well-being of working mothers who work from home during the Covid-19 pandemic in Bandung City is lower. Abstrak. Pandemi Covid-19 memiliki dampak yang cukup besar bagi subjective well-being pada ibu pekerja yang work from home. Keadaan pandemi Covid-19 memberikan kondisi yang kompleks pada ibu pekerja yang work from home sehingga menyebabkan distress, dimana ibu harus memantau dan mengontrol tugas-tugas sekolah anak, tugas rumah tangga, serta diharuskan bekerja secara jarak jauh dari rumah. Hal memberikan dampak psikologis bagi seorang ibu salah satunya adalah subjective well-being. Tujuan dari penelitian ini adalah melihat bagaimana gambaran subjective well-being seorang ibu pekerja work from home selama masa pandemi Covid-19 di Kota Bandung. Penelitian ini menggunakan metode deskriptif dengan pendekatan kuantitatif. Sampel penelitian ini adalah 300 orang, dengan menggunakan teknik purposive sampling. Pengukuran subjective well-being didapatkan melalui 2 alat ukur dari Diener, yaitu Satisfaction With Life Scale (SWLS) yang telah diadaptasi oleh Yusak Novanto dan Scale of Positive and Negative Experience (SPANE). Hasil dari dua alat ukur tersebut adalah 70% subjective well-being ibu pekerja work from home selama masa pandemi Covid-19 di Kota Bandung adalah rendah.